PENERAPAN TOTAL QUALITY MANAGEMENT (TQM) DALAM PENGELOLAAN MADRASAH: STUDI KUALITATIF DI MADRASAH DINIYAH SABILILLAH SYAICHONA CHOLIL SAMARINDA: STUDI KUALITATIF DI MADRASAH DINIYAH SABILILLAH SYAICHONA CHOLIL SAMARINDA - Hafidhoh, Siti Hafidhoh; Bahran (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe and analyze the implementation of Total Quality Management (TQM) in the management of Madrasah Diniyah Sabilillah Syaichona Cholil Samarinda. The research employs a qualitative approach with a case study method. Data were collected through observation, in-depth interviews, and documentation. The findings indicate that the implementation of TQM principles—such as customer focus (students and their parents), continuous improvement, and the involvement of all stakeholders—has been carried out gradually and consistently. Despite facing several challenges, such as limited resources and resistance to change, the madrasah has demonstrated significant improvements in the quality of its educational services. This study concludes that TQM can serve as an effective strategic approach to enhancing the quality of madrasah management. The implications of this research encourage Islamic educational institutions to adopt quality management approaches in their institutional governance.